Răspuns :
4 / √3 · √2 / 2 · 2014⁰ / √6
↓
=1
= 4√3 / 3 · √2 / 2 · 1 / √6 =
= ( 4 √3 ·√2 · 1 ) / ( 3 ·2 ·√6 ) =
= 4√6 / 6 ·√6 = 4 / 6 = 2 / 3
↓
√6 :√6 = 1
↓
=1
= 4√3 / 3 · √2 / 2 · 1 / √6 =
= ( 4 √3 ·√2 · 1 ) / ( 3 ·2 ·√6 ) =
= 4√6 / 6 ·√6 = 4 / 6 = 2 / 3
↓
√6 :√6 = 1
[tex] \frac{4}{ \sqrt{3} } * \frac{ \sqrt{2} }{2} * \frac{2014^{0} }{ \sqrt{6} } [/tex]=[tex] \frac{ 4\sqrt{3} }{3} * \frac{ \sqrt{2} }{2} * \frac{1}{ \sqrt{6} } = \frac{ 4\sqrt{3}* \sqrt{2}*1 }{3*2* \sqrt{6} }=\frac{ 4\sqrt{6} }{6 \sqrt{6} } = \frac{4}{6} = \frac{2}{3} [/tex]